2002
DOI: 10.3136/fstr.8.276
|View full text |Cite
|
Sign up to set email alerts
|

Oxydation of Quercetin by Salivary Components II. Effects of Quercetin on Reactive Oxygen Metabolism by Salivary Polymorphonuclear Leukocytes.

Abstract: Salivary polymorphonuclear leukocytes (SPMN) produce O 2-and H 2 O 2 reducing molecular oxygen, and quercetin is a phenolic compound found in vegetables and fruits. The aim of the present study was to elucidate the interaction between SPMN and quercetin. The oxygen consumption by SPMN, which was stimulated by phorbol myristate acetate (PMA), was suppressed by quercetin. Half-inhibition was observed at about 20 M quercetin. During inhibition of the oxygen uptake, quercetin was oxidized; the oxidation was inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It has been suggested that the H 2 O 2 /MPO system oxidizes nitrite (van der Vliet et al, 1997) and that polyphenols inhibit acidic nitritedependent nitration of tyrosine by scavenging nitrogen oxides (Oldreive et al, 1998). Quercetin was also oxidized by SPMN in the absence (Hirota et al, 2002) and presence of NaNO 2 (data not shown). Furthermore, it has been reported that quercetin (20-30 M) inhibits the oxygen consumption catalyzed by PMA-activated SPMN by 50% (Hirota et al, 2002).…”
mentioning
confidence: 80%
See 4 more Smart Citations
“…It has been suggested that the H 2 O 2 /MPO system oxidizes nitrite (van der Vliet et al, 1997) and that polyphenols inhibit acidic nitritedependent nitration of tyrosine by scavenging nitrogen oxides (Oldreive et al, 1998). Quercetin was also oxidized by SPMN in the absence (Hirota et al, 2002) and presence of NaNO 2 (data not shown). Furthermore, it has been reported that quercetin (20-30 M) inhibits the oxygen consumption catalyzed by PMA-activated SPMN by 50% (Hirota et al, 2002).…”
mentioning
confidence: 80%
“…4-Hydroxyphenylacetic acid (HPA) is also a component in the oral cavity although its origin remains to be elucidated . Since stimulated plasma polymorphonuclear leukocytes nitrate HPA to 4-hydroxy-3-nitrophenylacetic acid (NO 2 HPA) in the presence of nitrite (Halliwell et al, 1999;van der Vliet et al, 1997) and SPMN produces H 2 O 2 by stimulation (Hirota et al, 2002;Yamamoto et al, 1991), nitration of salivary HPA is probable if SPMN is accumulated and activated in the oral cavity.…”
mentioning
confidence: 99%
See 3 more Smart Citations